Hairy Polyp of the Supratonsillar Fossa Causing Intermittent Airway Obstruction - İsmi,Onur (2015)
Introduction Dermoids frequently called "hairy polyps" and their nature have not been completely clarified. Objectives To discuss the unusual presentation, symptoms, incidence, histology, and perioperative management of hairy polyps in the light of a case and current literature. Resumed Report A 3-year-old boy presented with intermittent respiratory distress since birth. Oropharyngeal examination revealed a nasopharyngeal mass originating from the supratonsillar fossa. The mass was so mobile that it moved between the oropharynx and the nasopharynx during swallowing. The radiologic and pathologic examinations confirmed the mass as a hairy polyp. Conclusion In a pediatric age group with airway obstruction, hairy polyps of the oropharyngeal region must also be included in the differential diagnosis.